CO2‐Induced 2D Ni‐BDC Metal–Organic Frameworks with Enhanced Photocatalytic CO2 Reduction Activity. Issue 13 (14th June 2021) - Chang, Hongwei; Zhou, Yannan; Zhang, Suoying; Zheng, Xiaoli; Xu, Qun
Abstract: The rational design of 2D metal–organic framework (MOF) nanosheets with high active exposed surfaces and ultrathin thickness is a critical issue for CO2 reduction. How to fabricate 2D MOFs and simultaneously fulfill the strong adsorption and activation of CO2 molecules is a great challenge. Here, it is reported that CO2 molecules can help to fabricate single‐layer [Ni3 (OH)2 (1, 4‐BDC)2 ‐(H2 O)4 ]·2H2 O, BDC = 1, 4‐benzenedicarboxylate, (Ni‐BDC) MOF nanosheets with large sizes and uniform thickness by exchanging with the coordinated H2 O molecules at Ni sites and further orientated chemically adsorption on it. CO2 molecules can not only help break the interlayer hydrogen bond of bulk materials realizing the successful transformation from 3D to 2D, but also contribute to expose the (200) planes with highly active in photocatalytic CO2 ‐to‐CO conversion, and a high production rate of 104 mmol g −1 h −1 and a high Faraday efficiency of 96.8% can be obtained. This strategy provides a novel prototypical model based on the strong interaction between metal active centers and reactive molecules to obtain 2D MOFs with high quality and activity. Abstract : 2D single‐layer [Ni3 (OH)2 (1, 4‐BDC)2 ‐(H2 O)4 ]·2H2 O, BDC = 1, 4‐benzenedicarboxylate (Ni‐BDC) metal–organic framework nanosheets with large sizes are synthesized through the strong interaction between CO2 molecules and Ni sites, which exhibit a high production rate of 104 mmol g −1 h −1 and a selectivity of 96.8% for CO in photocatalytic CO2 reduction.